2016
DOI: 10.1007/s00438-016-1171-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of WRKY family genes in peach and analysis of WRKY expression during bud dormancy

Abstract: Bud dormancy in deciduous fruit trees is an important adaptive mechanism for their survival in cold climates. The WRKY genes participate in several developmental and physiological processes, including dormancy. However, the dormancy mechanisms of WRKY genes have not been studied in detail. We conducted a genome-wide analysis and identified 58 WRKY genes in peach. These putative genes were located on all eight chromosomes. In bioinformatics analyses, we compared the sequences of WRKY genes from peach, rice, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 66 publications
6
40
0
Order By: Relevance
“…For comparative genomic analyses, we collected the WRKY protein coding genes in other plants from previous publications. Finally, 81, 59, 72, 52, 188, 62, 58, and 104 WRKY genes were collected from S. lycopersicum, V. vinifera, A. thaliana, C. papaya, G. max, F. vesca, P. persica, and P. trichocarpa, respectively [8][9][10][11][12][13][14][15][16]49]. The number of CcWRKY genes was similar to V. vinifera, C. papaya, F. vesca, and P. persica; but less than S. lycopersicum, A. thaliana, G. max, and P. trichocarpa (Figure 1).…”
Section: Isolation Of the Wrky Genes In C Canephoramentioning
confidence: 99%
See 1 more Smart Citation
“…For comparative genomic analyses, we collected the WRKY protein coding genes in other plants from previous publications. Finally, 81, 59, 72, 52, 188, 62, 58, and 104 WRKY genes were collected from S. lycopersicum, V. vinifera, A. thaliana, C. papaya, G. max, F. vesca, P. persica, and P. trichocarpa, respectively [8][9][10][11][12][13][14][15][16]49]. The number of CcWRKY genes was similar to V. vinifera, C. papaya, F. vesca, and P. persica; but less than S. lycopersicum, A. thaliana, G. max, and P. trichocarpa (Figure 1).…”
Section: Isolation Of the Wrky Genes In C Canephoramentioning
confidence: 99%
“…1845), wild strawberry (Fragaria vesca L.), soybean (Glycine max (L.) Merr. ), cucumber (Cucumis sativus L.), rice (Oryza sativa L.), stem-orchid (Dendrobium officinale Kimura et Migo), and the thorny shrub Caragana intermedia Kuang et H.C.Fu [3,[6][7][8][9][10][11][12][13][14][15][16]. Among them, many WRKY proteins have been cloned and shown to be associated with abiotic stress responses, such as cold [17,18], salt [19], and drought [20].…”
Section: Introductionmentioning
confidence: 99%
“…These are consistent with the classification of the WRKY family genes in Arabidopsis (Eulgem et al, 2000), maize (Wei et al, 2012), Populus (Jiang et al, 2014), cassava (Wei et al, 2016, and peach (Prunus persica) (Chen et al, 2016). All the WRKY genes can be classified into three distinct clusters: group I, II, and III depending on the number of conserved WRKY regions and the pattern of zinc-finger motif (Eulgem et al, 2000;Wei et al, 2012;Jiang et al, 2014).…”
Section: Discussionsupporting
confidence: 75%
“…In the present study, the number of introns found in the BvWRKY genes ranges from to 5, with an average of 2.79 introns per BvWRKY, so each BvWRKY sequence was divided into many segments by introns. Similarly, all of the WRKY genes in both cassava and peach have one to five introns (Wei et al, 2006;Chen et al, 2016). However, the SiWRKY genes in sesame have between 1 to 11 introns (Li et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation